Karyotypic analysis of the blunt-headed burrowing frog (Glyphoglossus molossus) using conventional staining and NOR-banding techniques - Sribenja, Kamika; Getlekha, Nuntaporn (Food Agricultural Sciences and Technology, 2026)
This study investigated the karyotype of the blunt-headed burrowing frog (Glyphoglossus molossus) using ten individuals (five males and five females) collected from Chombueng district, Ratchaburi province. Chromosome preparations were made from bone marrow cells, and mitotic chromosomes were obtained using a colchicine-hypotonic-fixation-air drying technique. Conventional staining was performed with 20% Giemsa’s solution to assess the diploid number, shape, and size of the chromosomes. The results revealed that the diploid chromosome number (2n) for the blunt-headed burrowing frog is 26, with the fundamental number (NF) of 52 in both males and females. The karyotype consists of 6 large metacentric chromosomes, 2 medium metacentric, 2 medium submetacentric, 12 small metacentric, and 4 small submetacentric chromosomes. NOR staining revealed a pair of NOR loci located at the subtelomeric region of the short arm of a submetacentric chromosome. Notably, no distinguishable sex chromosomes were observed. The karyotype formula for the species is 2n (26) = Lm6+ Mm2+Msm2+ Sm12+ Ssm4.